(untitled) (Research, Society and Development, 2022)
Breast cancer is a more frequent disease in women, being caused due to disordered cell multiplication. The study aims to demonstrate the main complications due to breast cancer in women. This is an integrative literature review, carried out from July to August 2022, through electronic searches in the Google Scholar database, being defined as inclusion criteria articles published in electronic format in the period between 2012 and 2022, available free of charge in Portuguese and that help in the discussion on the subject. Thus, 820 scientific articles were found and of these only 10 meet the inclusion criteria and research objectives. According to the results, it is found that breast cancer causes a series of physical and emotional consequences, which can directly impact the quality of life, causing changes in their family and social relationships, as well as blossoming feelings of helplessness and frustration. Therefore, it is concluded that breast cancer is a very serious disease that affects mainly the female audience, where the main complications found in the studies were depressive symptoms, psychological trauma, muscle weakness, loss of range of motion and sensitivity.